Dietary diversity and nutritional status among children in rural Burkina Faso. Issue 3 (22nd March 2018) - Sié, Ali; Tapsoba, Charlemagne; Dah, Clarisse; Ouermi, Lucienne; Zabre, Pascal; Bärnighausen, Till; Arzika, Ahmed M; Lebas, Elodie; Snyder, Blake M; Moe, Caitlin; Keenan, Jeremy D; Oldenburg, Catherine E
Abstract: Background: Burkina Faso has a seasonal malnutrition pattern, with higher malnutrition prevalence during the rainy season when crop yields are low. We investigated the association between dietary diversity and nutritional status among children aged 6–59 mo during the low crop yield season in rural Burkina Faso to assess the role of dietary diversity during the lean season on childhood nutritional status. Methods: Caregivers reported the dietary diversity of the past 7 d, consisting of 11 food groups, summed into a scale. Anthropometric measurements were taken from all children. Height-for-age (HAZ), weight-for-height (WHZ) and weight-for-age (WAZ) z-scores were calculated based on 2006 WHO standards. Stunting, wasting and underweight were defined as HAZ, WHZ and WAZ <−2 SD, respectively. Multivariable regression models adjusting for potential confounders including household food insecurity and animal ownership were used to assess the relationship between anthropometric indices and dietary diversity. Results: Of 251 children enrolled in the study, 20.6% were stunted, 10.0% wasted and 13.9% underweight. Greater dietary diversity was associated with greater HAZ (SD 0.14, 95% CI 0.04 to 0.25) among all children. There was no association between dietary diversity and wasting or mid-upper arm circumference in this study. Conclusions: Increasing dietary diversity may be an approach to reduce the burden of stunting and chronic malnutrition among young children in regions with seasonal food insecurity.